Recent research on late Mousterian sites in Dalmatia, Croatia - Karavanić, Ivor (Array, 2013)
Analyses from two famous Paleolithic sites in NW Croatia (Krapina and Vindija), are very well represented in international scientific publications. Unlike the vast research undertaken in NW Croatia (Hrvatsko Zagorje), the cultural sequence and paleoecology from the same period in Dalmatia (south Croatia) is poorly understood. Research of Paleolithic period in this region was sparse until recently. The only site in Dalmatia with a clear and homogenous Mousterian stratigraphic sequence that was exca - vated systematically (1995-2003) is Mujina Pećina near the city of Kaštela. Radiocarbon AMS and ESR dates obtained from Mujina Pećina are the first chronometric dates for the Mousterian industry on the eastern Adriatic coast. The interface between Level E2 and E1 was dated by AMS to 45ka BP, while the AMS age of overlying levels is about 39 ka BP (Rink et al. 2002). Another Dalmatian site, Velika Pećina in Kličevica near Benkovac, was first excavated in 2006 and continued in 2012. A short stratigraphic sequence was established, with several layers yielding rich Mousterian finds, and a single radiocarbon AMS date of about 39 ka BP. Kaštel Štafilić - Resnik is an open air Middle Paleolithic site from the period when the sea level was much lower than today. Small scale underwater excavation and systematic collection of surface finds at this site using a grid are ongoing since 2008. The methodology applied will be further described in the presenta - tion. Although no diagnostic fossil hominin remains have been found on Dalmatian Middle Paleolithic sites, the lithic assemblages (Mousterian industry) and the results of chronometric dating place their sequences con - temporary with the late Neanderthals and earliest known anatomically modern human groups in Europe. New research on Dalmatian sites makes a contribution towards our understanding of the distribution of Mousterian people and enables comparison with other Adriatic and continental sites.